Гендерні особливості віктимності підлітків - Шевченко, Л. О.; Селіванова, О. І.; Shevchenko, L. A.; Selivanova, O. I. (Право і безпека. - 2015. - № 3 (58). - С. 166–169., 2015)
Проаналізовано психологічні чинники й особливості віктимної поведінки в підлітковому віці. Розглянуто внутрішні детермінанти віктимності. Особливу увагу приділено гендерній специфіці прояву віктимної поведінки в підлітковому віці. Висвітлено особливості щодо профілактичної роботи з попередження віктимності.

The features of teenagers’ victimity considering gender component are analyzed. It is indicated that victimity has internal determinants such as psychodynamic basic characteristics of personality, reflecting an individual level of its functioning and programmable properties that form the content and semantic programs of behavior and activities of a human being, as well as external, which are a set of social conditions that have victimological potential. Teenager’s victimity occurs in the process of victimization. It is revealed that realized boys’ victimity is higher than girls’ one. Boys more often than girls suffer physical violence from parents, older boys and their peers, addicted to actively victim behavior and aggressive victim behavior, often deliberately create or provoke conflicts. They at a conscious level deny the existence of victimological qualities that really is not true. The model of passive victim behavior is inherent for girls in comparison with their boys-peers, who suffered psychological violence more often from both parents and peers. Despite the more critical attitude to themselves the most characteristic features of their behavior are addiction, fear of responsibility, setting for the helplessness, reconciliation with the role of a victim. Preventive measures concerning victim behavior of teenagers must have comprehensive nature, however, for girls and boys may need different preventive measures that promote the prevention of their victim behavior. The main tasks of prevention of teenagers’ victimity are to identify and consolidate the positive personality qualities, formation of the ability to make their own choices, sense of responsibility, timely resolution of conflicts.

Проанализированы психологические факторы и особенности виктимного поведения в подростковом возрасте. Рассмотрены внутренние детерминанты виктимности. Особое внимание уделено гендерной специфике проявления виктимного поведения в подростковом возрасте. Освещены особенности касательно профилактической работы по предупреждению виктимности.
Shevchenko, L.A. and Selivanova, O.I. (2015), “Gender features of teenagers’ victimity” [“Henderni osoblyvosti viktymnosti pidlitkiv”], Pravo i Bezpeka, No. 3, pp. 166–169.
Шевченко, Л. О. Гендерні особливості віктимності підлітків / Л. О. Шевченко, О. І. Селіванова // Право і безпека. - 2015. - № 3 (58). - С. 166–169.
Keywords: Кримінологія. Criminology. Криминология; Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; підлітки; віктимність; реалізована віктимність; гендер; жертва; teenagers; victimity; implemented victimity; gender; victim; несовершеннолетние; виктимность; реализованная виктимность